2021
DOI: 10.21037/jgo-20-568
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of programmed death ligant-1 expression in gastric cancer: a meta-analysis

Abstract: Background: Gastric cancer (GC) is a common malignant tumor with a high incidence in China. The use of immune checkpoint inhibitors has become the focus of tumor immunotherapy in recent years. This study was to investigate the clinicopathological and prognostic significance of programmed death ligant-1 (PD-L1) expression in GC. Methods: We searched the PubMed, ScienceNet, EMbase, CNKI, and Wanfang databases for retrospective cohort studies on the clinicopathology and prognosis of PD-L1 expression in GC publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…A more recent meta-analysis including 15 studies and 3218 patients from China, South Korea, Japan, and Germany, showed that PD-L1 expression was associated with a decrease in the 3-and 5-year survival rates. 52 In the subgroup analyses of ethnicity, PD-L1 expression in Asian patients was also associated with a decrease in the 3- and 5-year survival rates. PD-L1 expression was associated with lymph node metastasis but not with tumor staging.…”
Section: Biomarkers For Immune Checkpoint Inhibition In Gastric Cancermentioning
confidence: 92%
“…A more recent meta-analysis including 15 studies and 3218 patients from China, South Korea, Japan, and Germany, showed that PD-L1 expression was associated with a decrease in the 3-and 5-year survival rates. 52 In the subgroup analyses of ethnicity, PD-L1 expression in Asian patients was also associated with a decrease in the 3- and 5-year survival rates. PD-L1 expression was associated with lymph node metastasis but not with tumor staging.…”
Section: Biomarkers For Immune Checkpoint Inhibition In Gastric Cancermentioning
confidence: 92%
“…Several meta-analyses of the PD-L1 expression predictive value in GC have shown that PD-L1 expression is associated with a poor survival rate [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Immune Checkpoint Expression In Connection With Clinical Features and The Therapeutic Efficacy Of Their Inhibitionmentioning
confidence: 99%
“…For example, in a meta-analysis from Gu et al, an association of PD-L1 expression in GC with such clinical characteristics as the depth of tumor invasion ( p = 0.03), lymph node metastasis ( p = 0.03), venous invasion ( p = 0.0003), Epstein-Barr virus (EBV) infection ( p < 0.0001), microsatellite instability (MSI) ( p = 0.0001) was found [ 18 ]. In another meta-analysis, PD-L1 expression in GC was associated with lymph node metastasis (OR = 1.73, 95% CI = 1.18–2.54, p < 0.001) [ 17 ]. In the study of Zhang et al there was an association of PD-L1 expression with tumor size and lymph node metastasis [ 19 ].…”
Section: Immune Checkpoint Expression In Connection With Clinical Features and The Therapeutic Efficacy Of Their Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy can restore anti-tumor immune response, which can control and clear tumor cells ( 11 ). Currently, multiple meta-analyses have shown that the expression of PD-L1 on tumor cells exhibits predictive value for prognosis in a variety of tumors, including gastric cancer ( 12 ), malignant pleural mesothelioma ( 13 ), bone and soft tissue sarcomas ( 14 ), colorectal cancer ( 15 , 16 ), glioblastoma ( 17 ), nasopharyngeal carcinoma ( 18 ), and small cell lung cancer ( 19 ).…”
Section: Introductionmentioning
confidence: 99%